The Impact of Taste and Service Quality on Adolescents’ Purchase Decisions: A Study of Mie Gacoan in Padang City - Nabilla Bunga Syakhira; Ranggi Rahimul Insan; Anni Faridah; Wiwik Gusnita (Universitas Negeri Semarang, 2025)
This study examines the impact of taste and service quality on adolescents’ purchase decisions at Mie Gacoan in Padang City. The rising popularity of this restaurant among young consumers highlights the importance of understanding the key determinants of their purchasing behavior. Employing a quantitative associative approach with a cross-sectional survey design, data were collected from 100 respondents, determined using the Lemeshow formula under the assumption of an infinite population. Statistical analysis revealed that taste has a positive and significant effect on purchase decisions (t = 11.971; p < 0.05), while service quality also demonstrates a positive and significant influence (t = 6.033; p < 0.05). Furthermore, simultaneous testing confirmed that both variables collectively exert a positive and significant impact on purchase decisions (F = 220.563; p < 0.05). The findings underscore the critical role of maintaining consistent taste quality and enhancing service standards to strengthen adolescents’ purchasing behavior. Practical implications suggest that Mie Gacoan should prioritize flavor consistency, implement systematic staff training, and improve service efficiency to foster customer satisfaction and repeat patronage. These measures are expected to cultivate long-term loyalty among adolescent consumers. Future studies are encouraged to expand the research model by incorporating variables such as price, promotion, and brand image, thereby offering a more comprehensive understanding of fast-food purchase decisions among adolescents.